Engaged minority or quiet majority? Social intentions and actions related to offshore wind energy development in the United States. (February 2022) - Fleming, Chloe S.; Gonyo, Sarah Ball; Freitag, Amy; Goedeke, Theresa L.
Highlights: Analyses of awareness, support level, and intended action find two spatial clusters. Spatial clusters are termed engaged minority and quiet majority. Engaged minority is more likely to be aware of and opposed to offshore wind. Quiet majority is less likely to engage in past social action and intend action. Study offers three areas to improve offshore wind energy development processes. Abstract: This research examines the possibility of spatial variability of resident social action relative to the potential for offshore wind energy development in a subregion of the United States. Data were collected via a random household survey within coastal populations of North and South Carolina adjacent to proposed offshore wind energy development. Cluster analysis is used to create subgroups based on awareness, support level, and intended action. Perceived impacts, place attachment, and demographic characteristics are then examined between these spatial clusters. Residents of cluster 1 are more likely to be aware of and opposed to offshore wind energy development efforts, as well as more likely to have engaged in past action and intend action than residents of cluster 2. After examination of these and other differences between the groups, the two clusters are termed the "engaged minority" and "quiet majority." The authors then contextualize their findings to theorize the answers to two key questions: Why is the quiet majority less engaged and why is the engaged minority more opposed? Differences in awareness, opportunity, place attachment, perceived impacts, and demographics are explored, as are compounding barriers to social action, disenfranchisement, distrust, and perceived process fairness. Finally, management implications for potentially non-representative understandings of public opinion in energy development solutions are considered and recommendations for improved public engagement efforts related to offshore wind energy are discussed.